Millets as a Sustainable Crop for Nutritional Security: Addressing Malnutrition Challenges - Nidhi Taram; Aradhana Tirkey; O.P. Suryawanshi (International Journal of Nutritions, 2024)
Millets are cereal crops belonging to the Poaceae family, which is the scientific name for the grass family. They are classified into two main groups: major millets which include Sorghum, Pearl, Finger millet, and minor millets, such as Little, Foxtail, Proso, Barnyard, and Kodo millet. India is the chief producer of millets, with an annual production of more than 17 million tonnes. This accounts for 80% of Asia’s millet production and 20% of the global supply. Chhattisgarh is one of the states in India where minor millets like kodo millets, finger millets, and little millets are produced. These millets have several health benefits due to their nutrient content, including essential amino acids, antioxidants, dietary fiber, fatty acids like linolenic, oleic, and palmitic acid. Millets contain excellent nutritional value including macronutrients like protein (7–13%), carbohydrates (60–70%), fat (1.5–5%), fiber (2–7%). Little millet contains moisture (13.1%), protein (7.7%), carbohydrate (83.3%), fiber (11.5%), ash (2.7%), and fat (1.5%). Kodo millet contains moisture (11.92%), protein (11.52%), fat (2.89%), crude fiber (1.85%), ash (1.22%), and carbohydrate (70.60%). Finger millet contains carbohydrates (65–70%), fiber (2.5–3.5%), fat (1–1.5%), ash (2.5–3%), protein (5–8%), and moisture (11.75%). Sorghum millet contains moisture (11.9%), protein (10.4%), fat (1.9%), carbohydrate (72.6%), fiber (14.3%), and ash (1.6%). Barnyard millet contains crude protein (11.3–17.2%), fat (3.6–3.8%), ash (4.7–5.0%), crude fiber (5.41–6.87%), carbohydrate (68.8%), and moisture (8.7%). Foxtail millet contains moisture (9.35%), ash (3.10%), protein (10.29%), fat (3.06%), fiber (4.25%), and carbohydrate (69.95%). Pearl millet contains moisture (8.5%), crude protein (13.6%), crude fat (7.8%), crude fiber (2.8%), ash (2.1%), and carbohydrate (63.2%). Proso millet contains moisture (8.04%), crude protein (13.09%), fat (3.35%), crude fiber (2.37%), carbohydrate (77.33%), and ash (1.53%). Millet processing and value addition can offer a wide range of nutritious products to defeat the global issue malnutrition.
Keywords: Malnutrition; Millets; fiber; macronutrients; nutrients